Beauvoir and Writing as the Creation of the Self: Memoirs, Diaries, Biography. Issue 1 (1st June 2020) - Unknown
Abstract : Kate Kirkpatrick, Becoming Beauvoir: A Life (London: Bloomsbury, 2019), xiv +476 pp. ISBN: 9781–350–04717–4 Simone de Beauvoir, Diary of a Philosophy Student: Volume 2, 1928–29 . The Beauvoir Series. Edited by Barbara Klaw, Sylvie Le Bon de Beauvoir, Margaret Simons, and Marybeth Timmerman; translated by Barbara Klaw; series edited by Margaret Simons and Sylvie Le Bon de Beauvoir (Urbana: University of Illinois Press, 2019), xii +374 pp. ISBN: 978–0-252–04254–6